Assessing the non-payment of service charges and its effects on service delivery in Elias Motswaledi Local Municipality - Rahlagane, Koketso Gladys (My University, 2021)
The aim of this study was to assess the impact and the effect of non–payment of municipal services on service delivery in the Elias Motsoaledi Local Municipality. The municipalities as the lowest part of Government are responsible for delivering basic services like water supply, electricity, road maintenance, refuse collection and sanitation to communities. Legislation permits municipalities to charge for services rendered. The study adopted the qualitative and quantitative research methods for data collection and analysis. Households in the selected villages (Motetema, Tambo and Groblersdal), were randomly selected to participate in the study and also the officials from the Elias Motsoaledi Local Municipality. Non-payment of municipal services is a great challenge in South African local government and threaten the financial viability and proper service delivery. Communities are protesting daily in service delivery outcries. The municipalities are struggling to collect revenue; they basically depend on the grants from the national Treasury. This dissertation probes the nature of non-payment of municipal services, its impact on service delivery and the methods used to tackle non-payments and to recommend the workable solutions. The findings of this study reveal that indeed revenue collection and non-payment of municipal service charges is a challenge in Elias Motsoaledi Local Municipality and it is having a dire impact on effective service delivery. This is due to unwillingness to pay for service charges, unemployment, poor quality services, low income amongst other challenges. Thus, the municipality is unable to generate adequate revenue to deliver better services. The study, therefore, gives recommendations on how the Municipality can improve revenue collection and mitigate non-payment of service charges
Thesis (MPA.) -- University of Limpopo, 2021
Keywords: Service delivery non-payments; Service charges; Elias Motswaledi Local Municipality; Local government; Local government -- South Africa -- Congresses; Municipal services -- South Africa -- Limpopo